The Black bard of North Carolina : George Moses Horton and his poetry - Horton, George Moses, 1798?-approximately 1880 (Slavery in America and the world: history, culture & law., 1997)
For his humanistic religious verse, his poignant and deeply personal antislavery poems, his folk verse, and, above all, his lifelong enthusiasm for liberty, nature, and the art of poetry, George Moses Horton merits a place of distinction among nineteenth-century African American poets. Enslaved for sixty-eight years - from his birth until the close of the Civil War - he was the first American slave to protest his bondage in published verse, the first black man to publish. A book in the South, and the only slave to earn a significant income through the sale of his poems. As a man and as a poet, Horton's achievements were extraordinary. In this volume, Joan Sherman collects sixty-two of Horton's poems. Her comprehensive introduction - which combines biography, history, cultural commentary, and critical insight - presents a compelling and detailed picture of this remarkable man's life and art. Covering a wide range of poetical subjects in. Varied verse forms, this collection is an eloquent testament to Horton's unique voice.